Efektivitas Penerimaan Pajak Hotel dan Pajak Restoran Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Tapanuli Utara Tahun 2015-2023 - Wasti Ratu Simamora; Etik Umiyati; Rosmeli Rosmeli (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This research aims to:1) To understand and analyze development of revenue, hotel tax and restaurant tax in North Tapanuli Utara from 2015-2023. 2) To understand and analyze the effectiveness, hotel tax, restaurant tax effectiveness, hotel tax efficiency, and restaurant tax efficiency in North Tapanuli Regency. This study uses time series data from 2015-2023, wihich is secondary data, to assess the efectiviness of hotel tax and restaurant tax revenue on local revenue (PAD) in North Tapanuli Regency. The data collection method used is library research, which utilizes literature or library materials as the primary data source. Quantitative descriptive analysis methods are used determine the develoment of PAD, tax development, restaurant tax development, hotel tax effectiveness, tax efficiency, and restaurant tax efficiency. The results of this study provide an overview of the development of PAD, development of hotel taxes, the development of restaurant taxes, the effectiveness of hotel tax revenue, restaurant taxes, hotel tax efficiency towards the original regional income (PAD) of North Tapanuli Utara Regency in 2015-2023. The average development of PAD in North Tapanuli regency is 10 percent, the average development of hotel taxes is 4 percent and the average development of restaurant taxes is 19 percent. The average effectiveness is 89 percent, which is classified as quite effective, the effectiveness of restaurant taxes reaches 91 percent which is classified as effective. The efficiency of hotel taxes is 5 percent which is classified as inefficient, while the efficiency of restaurant taxes is 107 percent which is classified as very efficient.